Inhibition of Kupffer Cell Autophagy Abrogates Nanoparticle‐Induced Liver Injury. Issue 9 (24th February 2017) - Zhu, Shasha; Zhang, Jiqian; Zhang, Li; Ma, Wentao; Man, Na; Liu, Yiming; Zhou, Wei; Lin, Jun; Wei, Pengfei; Jin, Peipei; Zhang, Yunjiao; Hu, Yi; et al.
Abstract : The possible adverse effects of engineered nanomaterials on human health raise increasing concern as our research on nanosafety intensifies. Upon entry into a human body, whether intended for a theranostic purpose or through unintended exposure, nanomaterials tend to accumulate in the liver, leading to hepatic damage. A variety of nanoparticles, including rare earth upconversion nanoparticles (UCNs), have been reported to elicit hepatotoxicity, in most cases through inducing immune response or activating reactive oxygen species. Many of these nanoparticles also induce autophagy, and autophagy inhibition has been shown to decrease UCN‐induced liver damage. Herein, using UCNs as a model engineered nanomaterial, this study uncovers a critical role for Kupffer cells in nanomaterial‐induced liver toxicity, as depletion of Kupffer cells significantly exacerbates UCN‐induced liver injury. Furthermore, UCN‐induced prodeath autophagy in Kupffer cells, and inhibition of autophagy with 3‐MA, a well‐established chemical inhibitor of autophagy, enhances Kupffer cell survival and further abrogates UCN‐induced liver toxicity. The results reveal the critical importance of Kupffer cell autophagy for nanoparticle‐induced liver damage, and inhibition of autophagy may constitute a novel strategy for abrogating nanomaterial‐elicited liver toxicity. Abstract : Kupffer cells prevent upconversion nanoparticles (UCNs) diffusion to hepatocytes and protect liver from nano‐hepatotoxicity . Large dose of UCNs deplete Kupffer cells and escape out of sinusoids to hepatocytes, further induce hepatotoxicity. Inhibiting the autophagy of Kupffer cells promotes cells survival and diminishes the uptake of UCNs by hepatocytes, thereby abrogating the nano‐hepatotoxicity.